Giα proteins exhibit functional differences in the activation of ERK1/2, Akt and mTORC1 by growth factors in normal and breast cancer cells - Wang, Zhanwei (2014)
Background In a classic model, Giα proteins including Gi1α, Gi2α and Gi3α are important for transducing signals from Giα protein-coupled receptors (GiαPCRs) to their downstream cascades in response to hormones and neurotransmitters. Our previous study has suggested that Gi1α, Gi2α and Gi3α are also important for the activation of the PI3K/Akt/mTORC1 pathway by epidermal growth factor (EGF) and its family members. However, a genetic role of these Giα proteins in the activation of extracellular signal-regulated protein kinase 1 and 2 (ERK1/2) by EGF is largely unknown. Further, it is not clear whether these Giα proteins are also engaged in the activation of both the Akt/mTORC1 and ERK1/2 pathways by other growth factor family members. Additionally, a role of these Giα proteins in breast cancer remains to be elucidated. Results We found that Gi1/3 deficient MEFs with the low expression level of Gi2α showed defective ERK1/2 activation by EGFs, IGF-1 and insulin, and Akt and mTORC1 activation by EGFs and FGFs. Gi1/2/3 knockdown breast cancer cells exhibited a similar defect in the activations and a defect in in vitro growth and invasion. The Giα proteins associated with RTKs, Gab1, FRS2 and Shp2 in breast cancer cells and their ablation impaired Gab1’s interactions with Shp2 in response to EGF and IGF-1, or with FRS2 and Grb2 in response to bFGF. Conclusions Giα proteins differentially regulate the activation of Akt, mTORC1 and ERK1/2 by different families of growth factors. Giα proteins are important for breast cancer cell growth and invasion.